Formation of Religious Character through the Takhasus Memorization Program - Yunitasari, Galuh Asmarani; Kamil, Achmad Muhammad (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Letiges & Association of Muslim Community in ASEAN (AMCA), 2025)
This study examines the process of religious character formation with the Takhasus memorization program. The study was conducted at SD Hj. Isriati Baiturrahman 2 Semarang. The research method used is field research with a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. Teachers and students are the subjects of this study. Data analysis uses the steps of data reduction, presentation and verification. The Takhasus memorization program includes memorizing the Qur'an (juz 'amma), authentic al-Ḥadis, and daily prayers, carried out routinely every morning before learning begins. The Takhasus memorization program is essential in forming students' religious character, such as increasing faith, piety, and noble morals. In addition, other characteristics that are also formed include discipline, responsibility, hard work, independence, and a love of reading. This habit has an impact on increasing mutual respect among fellow students. The success of this program is influenced by family support and teacher consistency in implementing habits. This program is part of the school's strategy to instill Islamic values ​​in students early, benefiting their spiritual development and forming better character. In addition, character education also includes spiritual awareness, namely awareness of the presence of God and developing love and fear for Him. In this context, individuals must focus on growing their character and prioritizing moral and ethical values ​​. Thus, the memorization program can be a model for other schools that want to integrate religious and character education into the learning process. This study contributes to the world of education by developing similar programs that focus on forming students' religious character.